Mitochondrial genes reveal triatoma jatai as a sister species to triatoma costalimai (Reduviidae: Triatominae) - Teves, Simone Caldas; Gardim, Sueli [UNESP]; De La Fuente, Ana Laura Carbajal; Lopes, Catarina Macedo; Gonçalves, Teresa Cristina Monte; Dos Santos Mallet, Jacenir Reis; Da Rosa, João Aristeu [UNESP]; Almeida, Carlos Eduardo [UNESP] (American Society of Tropical Medicine and Hygiene, 2016)
Triatoma jatai was described using a set of morphological structures from specimens collected in Paranã municipality of Tocantins State, Brazil. Under a Bayesian framework and using two mitochondrial genes (16S and COI), phylogenetic analysis recovered T. jatai as a sister species to Triatoma costalimai with higher genetic distances than between other well-recognized species. Our results agree with previous suggestions based on morphometric analysis. In the light of the non-monophyly of Matogrossensis subcomplex, the inclusion of T. jatai shall be considered for reevaluating this group.